Comparison of Corneal Biomechanics in Post-SMILE, Post-LASEK, and Keratoconic Eyes - Shang, Jianmin; Shen, Yang; Jhanji, Vishal; Zhou, Xueyi; Zhao, Jing; Zhao, Yu; Zhou, Xingtao (Frontiers in Medicine, 2021)
Significance: Our study found that SP-A1(stiffness parameter at time of first applanation) was statistically different between post-LASEK and post-SMILE eyes. The stiffness of keratoconus was lower than post-refractive surgery corneas. Purpose: To compare corneal biomechanics among post-SMILE (Small incision lenticule extraction), post-LASEK (Laser-assisted subepithelial keratomileusis) and keratoconic eyes. Methods: In this retrospective study, 36 eyes of 36 patients after SMILE, 36 eyes of 36 patients after LASEK, and 36 eyes of 36 patients with keratoconus with matching (±5μm) central corneal thickness (CCT), were examined using Scheimpflug corneal topography (Pentacam HR) and dynamic Scheimpflug analyzer (CorVis ST). Mixed linear model analysis with Bonferroni-adjusted post-hoc comparisons was performed to compare the differences in corneal biomechanics and topographic parameters among the three groups with the CCT and the bIOP (Intraocular pressure with biomechanical correction) as the random factor. Results: All groups had comparable CCT at baseline. The bIOP between the three groups were comparable. The mean values of Belin/Ambrósio Deviation value (BAD-D) in the keratoconus Group was significantly higher than SMILE (Post hoc P<.001) and LASEK groups (Post hoc P<.001). The SP-A1 in the keratoconus group was the lowest when compared with SMILE (Post hoc P=.003) and LASEK groups (Post hoc P<.001). The SMILE group SP-A1 values were slightly lower than that of LASEK group (post hoc P=.044). Conclusions: Keratoconus eyes were significantly softer when compared to post-refractive surgery corneas with comparable corneal thickness in terms of SP-A1 and BAD-D values, while LASEK group may have the greatest stiffness. Post-SMILE and post-LASEK corneas showed significant differences in SP-A1.